Real-time Protection Scheme for Distribution Networks Connected with Distributed Generation - Gee, Chong Chea; Mokhlis, Hazlie (New Explorations in Electrical Engineering, 2025)
This research proposes a real-time protection scheme for distribution networks with distributed generation, offering critical insights for benchmarking protection levels against established guidelines. The project aims to (1) propose optimal protection coordination, (2) update settings for network changes in distribution systems, and (3) integrate the protection scheme with an active management system. The first objective involves using a detailed model and optimization algorithms to design a protection coordination scheme that minimizes fault clearance times while ensuring selectivity and preventing unnecessary outages. This model also allows seamless updates to accommodate system changes, ensuring continued effectiveness in a dynamic environment. The third objective emphasizes using the model to bridge the real-time protection scheme with the active management system, enabling proactive interventions and preventive measures. Overall, this research not only introduces a novel real-time protection scheme but also integrates it within a larger framework for proactive risk management and dynamic adaptation, enhancing the reliability and resilience of distribution networks.